Criminal Liability Against Corporations in Payment of Wages Under the Provisions of Legislation - Ida Hanifah (International Journal Reglement & Society (IJRS), 2022)
As a legal subject, corporations have responsibilities as regulated in Law No. 13 of 2003. Manpower is either a legal entity or not. In the Manpower Act, corporate responsibility consists of two, namely; administrative sanctions as well as criminal sanctions. The criminal sanctions applied are in the form of imprisonment and fines. The criminal liability of corporations used by the law is in the form of